Formation of multifunctional nano-layered oxide REE-containing materials using nitrate precursors - Dryuchko, Оleksandr; Storozhenko, Dmytro; Bunyakina, Natalya; Ivanytska, Iryna; Khanyukov, Vasyl; Kytayhora, Кateryna (Academic journal Industrial Machine Building Civil Engineering, 2019)
Complex system research of the interaction of structural components in nitrate systems of rare-earth and IA, IIA elements ofthe periodic system – precursors of modern multicomponent oxide polyfunctional materials on their basis – established theformation of a class of lanthanides alkaline coordination nitrates. The obtained data are the basis for identifying, controllingthe formed phases in the preparatory stages of processing in innovative technologies using nitrate predecessors of differentelectronic structures elements and various combinational methods of their activation, establishing technological andfunctional dependencies, controlling the modification of the synthesis products properties.
Keywords: alkaline coordination nitrates of lanthanides; formation conditions; crystal structure of compounds; properties